Stable isotope forensics: methods and forensic applications of stable isotope analysis - Meier-Augenstein, Wolfram (Developments in forensic science, 2018)
Cover ; Title Page ; Copyright ; Contents ; Series Foreword; Foreword: Dame Sue Black; Foreword: Mark Harrison; Foreword to the 1 Edition; Book Endorsements; Preface to the 2 Edition; List of Abbreviations; About the CompanionWebsite; Introduction: Stable Isotope 'Profiling' or Chemical 'DNA': A New Dawn for Forensic Chemistry?; Part I How it Works; Chapter I.1 What are Stable Isotopes?